HIV-related stigma and social capital in South Africa. - Chiu, Jessica; Grobbelaar, Janice; Sikkema, Kathy; Vandormoel, Alain; Bomela, Nolunckwe; Kershaw, Trace (AIDS education and prevention : official publication of the International Society for AIDS Education, 2008)
Few studies have considered the relationship between social capital and stigmatizing attitudes. The aim of this study is to assess the relationship between HIV stigmatizing attitudes and individual perceptions of social capital in South Africa. The study surveyed 619 community members to assess whether social capital predicted personal and attributed HIV stigmatizing attitudes. Personal stigma was defined as the individual's own attitude toward people with HIV and attributed stigma were those attitudes that the individual perceived as existing in their communities. Results showed that social capital components significantly predicted personal and attributed stigma above and beyond demographic covariates and whether the participant knew someone with HIV. Individual social capital components of empowerment, trust, and group membership related to personal stigma; and safety, trust, and homogeneity of residential area related to attributed stigma.
Keywords: Adolescent; Adult; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Interviews as Topic; Linear Models; Male; Middle Aged; Prejudice; Social Support; South Africa; Stereotyping